A revision of the current elective courses of the B.A. in English language teaching of the Foreign Language Department at the University of El Salvador, semesters I and II - 2018: a proposal for curriculum change - Villatoro Huezo, Gabriela Alejandra; Martínez Hernández, Dany Alexander; Cardoza Alvarado, Karina Rosibel (2024)
The University of El Salvador has different requirements for students to earn a degree and offers all of the required courses every semester. When it comes to taking college classes there is a certain degree of planning and forethought required. Nowadays, college degree programs are becoming critical aspects of a successful career. Therefore, in the University of El Salvador students require a blend of both core courses that are focused on their degree program and elective courses that expand on their interests and fundamental critical thinking skills. Core courses include subjects that teach necessary and valuable information that are directly related to their field of study. On the other hand, the elective courses are those offered throughout the major as per student’s election, which means that a group of courses is presented out of which the student can freely choose which ones to course base on their academic needs or personal bias. Furthermore, the need of making a revision on the elective courses offered on the major of English in every specific semester is really essential due to the fact that most of the syllabi provided by a college or university have direct consequences on the learning development of the students and; therefore, these courses have to be aligned with the current society demands and laws. There are some reasons why some elective courses should be considered to be added on the current curriculum of the B.A in English. One of the strongest reasons is that some elective courses provide ways for students to increase their knowledge in a specific area on the foreign language. Moreover, some elective courses are the key for students to make a decision on studying a master’s degree (for example a master’s degree in translation).